Peningkatan Kemampuan Berpikir Kritis dan Penyelesaian Masalah Melalui Model Problem Based Learning (PBL) pada Pembelajaran Tematik Kelas VI SDN 19 Cakranegara - Siti Nurbaya (Pendagogia: Jurnal Pendidikan Dasar, 2021)
The ability to think critically and solve HOTS questions for grade VI students of SDN 19 Cakranegara for the 2019/2020 academic year is not as expected. This condition can be seen from the number of students who have not met the Minimum Completeness Criteria for MTK subjects, which is 70. This problem occurs because of the lack of critical thinking skills and problem solving on HOTS-based math problems. To overcome this, researchers made improvements using a problem based learning (PBL) model. This study aims to improve critical thinking skills and problem solving HOTS questions for grade VI students of SDN 19 Cakranegara by applying a problem based learning (PBL) model. This type of research is Classroom Action Research which is carried out in 2 cycles, each cycle consists of 4 stages, namely planning, implementing actions, observing and evaluating, and reflecting. The subjects of this study were students of class VI. Data on students' critical thinking and problem solving abilities were collected through written tests given at the end of each cycle. Based on the results of the study obtained data on increasing students' critical thinking skills in the first cycle of 6.81%, increasing in the second cycle of 9.46%. In addition, there was an increase in student problem solving in the first cycle of 10.14%, an increase in the second cycle of 11.96%. The conclusion of this study is that the application of the problem based learning (PBL) model can improve critical thinking skills and problem solving HOTS questions for class VI SDN 19 Cakranegara Academic Year 2019/2020.